On the measurement of linear viscoelastic moduli. A comparison between oscillatory tests - Rubio-Hernández, Francisco José; Rodríguez Lara, Miriam; Velázquez-Navarro, José Francisco; Sánchez Rodríguez Jesús (My University, 2025)
An essential task in the study of the linear viscoelastic behavior in structured liquids is the determination of the G’ and G’’ moduli, since they provide information about which part of the material response under load is due to its elastic and viscous part, respectively [1]. Traditionally, to measure these parameters, an oscillating shear is applied to a small sample contained between a fixed flat plate and a geometry which, when rotated, generates a controlled shear with a predefined amplitude and frequency. Another approach is explored in this work consisting in applying an oscillating load to the sample perpendicular axis or, in other words, "squeezing" it. From this method both moduli can be derived from the experimental force and deformation data [2], allowing the comparative between methods. The values obtained from these two methods show an excellent agreement, opening the possibility of extending the study of linear viscoelasticity to materials that, due to their characteristics (e.g. suspensions with large particles in suspension, semi-solids, etc.) are difficult to measure adequately in rotational rheometers. [1] Barnes, H. A., Hutton, J. F., & Walters, K. (1989). An introduction to rheology (Vol. 3). Elsevier. [2] Bell, D., Binding, D. M., & Walters, K. (2006). The oscillatory squeeze flow rheometer: comprehensive theory and a new experimental facility. Rheologica acta, 46(1), 111-121.
Keywords: Reología - Congresos; Viscoelasticidad